The Position of Debtor Legal Protection for Bankruptcy of Separatist Creditors - Herman Yusuf; Achmad Sulchan; Umar Ma'ruf; R. Sugiharto (Sultan Agung Notary Law Review, 2022)
The position of the debtor who is bankrupted by the preference rights of the creditor results in injustice, especially in terms of the legal protection of the debtor. The revision of Act No. 4 of 1998 to Act No. 37 of 2004 contained a conflict of norms in it. The purpose of this research is to analyze and find out: 1).Implementation of debtor legal protection against bankruptcy carried out by current separatist creditors. 2). Factors that affect the implementation of legal protection for debtors against bankruptcy carried out by separatist creditors. 3) Implementation of legal protection for debtors for bankruptcy carried out by separatist creditors. The approach method in this research was normative juridical. The data used was secondary data obtained through literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1) The implementation of debtor legal protection for bankruptcy carried out by separatist creditors currently as intended by Article 55 and Article 56 of Act No. 37 of 2004 has not been fair to debtors, considering that the two articles are only based on the existence of debt from the debtor and related to the position of the solvent or insolvency based on the view of the creditor alone. This is clearly the case because Act No. 37 of 2004 does not adhere to a balance sheet test system where before being declared bankrupt it is necessary to test the condition of the debtor whether it is really insolvent or actually still solvent. 2) Factors influencing the implementation of debtor legal protection for bankruptcy carried out by separatist creditors are legal factors, namely the existence of provisions in Article 55 and Article 56 of Act No. 37 of 2004 which are unfair to debtors, legal implementation factors are in the form of a culture judges as mouthpieces of the law even though it is well known that the door to justice in bankruptcy cases is the judge's decision. 3) Implementation of debtor legal protection for bankruptcy carried out by separatist creditors which should be in order to realize protection for debtors related to the execution of parate by creditors, it is necessary to renew the concept of bankruptcy law in Indonesia.